Public Enterprise Reform and Privatization in Korea: Lessons for Developing Countries - Wonhyuk Lim (Korea Development Institute (KDI), 2003)
A Corporate Governance Perspective on Public Enterprises In its broad sense, corporate governance may be defined as the entire set of institutions, both inside and outside the firm, through which the objectives of the company are set and executed and the performance of the firm is monitored. From a corporate governance perspective, incentive schemes and objectives under public vs. private provision may be analyzed as follows. For public provision, the objective is "public interest," defined through a political process; whereas, for private provision, the objective is profit. However, for both public and private provision, the most effective incentive mechanism for managers is to link managerial rewards to performance, based on clearly defined objectives. The essence of public enterprise reform prior to privatization is to establish this type of effective incentive mechanism by implementing the following set of actions: (1) Minimize political interference, especially in personnel and pricing decisions; (2) Clarify the firm's objectives, using performance indicators whenever possible; (3) Increase managerial autonomy to meet these objectives; (4) Evaluate managerial performance; (5) Link reward to performance. Privatization makes a fundamental break from this approach and changes the objective of the firm from "public interest" to "profit." As such, a decision to privatize a public enterprise should be based on a judgement that the firm's "public interest" function has been exhausted or can be replaced by other means such as direct fiscal subsidies. There should also be an additional judgment that the introduction of the profit motive through privatization is likely to lead to increased consumer welfare through substantive competition and regulation. Privatization will risk a serious backlash if it leads to a destruction of firm value through "tunneling" or other acts of malfeasance, or gives rise to monopoly rent due to the lack of competition or the capture of regulatory bodies. As the effectiveness of privatization crucially depends on the existence of competitive and efficient markets, privatization should be part of a comprehensive program of market-oriented reform.
Keywords: 330